The thermal bioeffects of prenatal ultrasound on rabbit newborns: body weight analysis - Amran, Umi Nadrah; Ahmad Zaiki, Farah Wahida (Kulliyyah of Allied Health Sciences, International Islamic University Malaysia, 2020)
Introduction: The Doppler mode is associated with higher acoustic output which leads to a greater conversion of energy into heat. This is due to the fact that the Doppler ultrasound beam is focused and localized at a particular area of interest. The energy in an area is converted to heat which accumulates and increases the tissue temperature at the localized area. Since heat is considered as a teratogen in pregnancy, any thermal bioeffects can be fatal to fetuses. Aim: This study aims to investigate the thermal bioeffects of using the Doppler ultrasound on the weights of newborn rabbits. Method: Twelve pregnant New Zealand White rabbits were exposed once at three gestational stages using three different exposure durations. After delivery, the mean weights of the newborns were analysed using the Statistical Package for the Social Sciences (SPSS). Results: This study found that longer periods of fetal exposure to the Doppler ultrasound resulted in thermal bioeffects in which a decrease in newborn body weight can be seen in the early (1st and 2nd) gestational stages (GS) prolonged Doppler exposure. Longer periods of exposure to the Doppler ultrasound increased the risk of thermal bioeffects. Conclusion: It is recommended that health practitioners limit fetal exposure to Doppler ultrasound to minimise the potential bioeffect risks.